PENGARUH GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP DISIPLIN KERJA DENGAN KEPUASAN KERJA SEBAGAI MEDIASI PADA PERUSAHAAN PT MULYA REZKINA SEJAHTERA - Afifah; Fahmy, Rahmi; Rahman, Hafiz (ITB AAS Indonesia Surakarta, 2025)
Every activity carried out in an organization requires human resources to run the organization so that it can continue to grow and develop to achieve the goals that have been set. Employees as human resources in an organization, with all their competencies or abilities and knowledge tend to be able to understand their responsibilities to carry out and complete their tasks well. In addition to competence, every organization also needs employees who have good work discipline. This study aims to determine the effect of leadership style and organizational commitment on work discipline with job satisfaction as a mediator.The method used in this study is explanatory research. The population in this study were employees of PT. Mulya Rezkina Sejahtera totaling 120 people. This study uses Partial Least Square in analyzing the data. The results of this study are that leadership style and organizational commitment have a positive and significant effect on job satisfaction. Job satisfaction has a negative and insignificant effect on work discipline. Leadership style and organizational commitment have a positive and significant effect on work discipline. Leadership style is moderated by job satisfaction has a negative and insignificant effect on work discipline. Organizational commitment is moderated by job satisfaction has a negative and insignificant effect on work discipline.